Contact dermatitis - Johansen, J. D. (Jeanne Duus).; Frosch, Peter J.; Lepoittevin, J.-P 1959- (Jean-Pierre).; SpringerLink (Online service). (Berlin Springer, 2011)
The fifth edition of Contact Dermatitis covers in detail every conceivable aspect of irritant and allergic contact dermatitis and its modern-day management. Special emphasis is given to immunological mechanisms, molecular aspects of sensitizers, atypical clinical forms, reactions to medicaments, and occupational and environmental factors. In order to optimize the diagnostic approach, a wide range of information is provided, including a dictionary of contact allergens. Retained chapters from the previous edition have been thoroughly revised to reflect the latest knowledge. Furthermore, completely new chapters have been added on a variety of topics, including genetics, the role of the skin barrier, the link between respiratory symptoms triggered by chemicals and contact dermatitis, and prevention. The editors and authors are all leading practitioners in the field. The comprehensive but approachable text is supplemented by a large number of full color illustrations and tables. Core messages highlight the most important information and will help the reader to gain a better understanding of the subject and greater competence in everyday practice.
Part 5 Diagnostic Tests -- Patch Testing -- Atopy Patch Testing with Aeroallergens and Food Proteins -- Patch Testing in Adverse Drug Reactions -- Allergens Exposure Assessment -- Skin Tests for Immediate Hypersensitivity -- Photopatch Testing -- Noninvasive Techniques for Quantification of Contact Dermatitis -- Part 6 Allergic Contact Dermatitis Related to Specific Exposures -- Allergens from the European Baseline Series -- Cosmetics and Skin Care Products -- Fragrances -- Hair Dyes -- Metals -- Metalworking Fluids -- Plastic Materials -- Topical Drugs -- Dental Materials -- Clothing -- Shoes -- Occupational Contact Dermatitis -- Occupational Contact Dermatitis Health Personnel -- Occupational Contact Dermatitis Chefs and Food Handlers -- Occupational Contact Dermatitis: Hairdressers -- Plants and Plant Products -- Pesticides -- Contact Allergy in Children -- Therapy and Rehabilitation of Allergic and Irritant Contact Dermatitis -- Prevention of Hand Eczema Gloves, Barrier Creams and Workers Education -- Prevention of Allergic Contact Dermatitis: Safe Exposure Levels of Sensitizers -- Legislation -- International Comparison of Legal Aspects of Workers Compensation for Occupational Contact Dermatitis -- Databases and Networks. The Benefit for Research and Quality Assurance in Patch Testing -- Contact Dermatitis Research Groups -- Patch Test Concentrations and Vehicles for Testing Contact Allergens -- Patch Testing with the Patients Own Products -- Dictionary of Contact Allergens: Chemical Structures, Sources, and References.
Electronic reproduction.
Keywords: Contact dermatitis; Dermatitis, Contact; Electronic books